(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
The paper explores the negative theology employed in John (Scott) Eriugena’s work “On the division of nature” as a core structure in his ontological system. Apophatic stances are crucial in Eriugena’s exposition of the position and role of God, and thus in the intricate functioning of the four divisions of nature and his concept of the five modes of interpretation of being. The basic categories in his system of nature are shown, along with the most poignant claims of the ineffability and unknowability of God, in order to then analyse his framework of kataphatic and apophatic theologies in approaching the inaccessible, super-essential, incomprehensible nature of the divinity. Eriugena’s opinions on the values and workings of the two branches of theology place them not in conflict or disagreement with one another, but as complementary and in constant harmony. A major part of the paper deals with Eriugena’s preference for the negations of the apophatic theology when talking about God, paired with an obvious awareness that the merits of the kataphatic theology are also substantial in expressing a trace of God as a manifestation in the created world; as well as with his dialectical manoeuvre of stressing the significance of the more-than formulateons for God’s super-essentiality. Therefore, Eriugena’s ideas on the formulae that are affirmative in form, but negative in meaning will be overviewed, in order to show his take on the advantages of the synthesis of the kataphatic and the apophatic theologies, in the form of a “hyperphatic” theology expressing God as non-expressible (because more-than-expressible).